2021
DOI: 10.1001/jamanetworkopen.2021.38414
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Adverse Maternal Outcomes in Pregnant Women With Disabilities

Abstract: IMPORTANCEWomen with disabilities have a higher risk of preterm birth, gestational diabetes, preeclampsia, and cesarean delivery; however, their risk of other obstetric interventions, adverse maternal outcomes, and clinical indications for increased cesarean delivery is unclear. OBJECTIVE To evaluate risk of a range of obstetric interventions and adverse maternal outcomes, including severe maternal morbidities (SMM) and mortality, among women with and without disabilities. DESIGN, SETTING, AND PARTICIPANTS The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
(77 reference statements)
1
23
0
Order By: Relevance
“…This study builds on recent findings indicating that women with disabilities are at greater risk for SMM and/or mortality than women without disabilities 11–13 Brown et al 13 also found that risk was greater for women with IDD than for those with physical or sensory disabilities. We found similar patterns of increased risk for SMM among women with disabilities overall, and greater risk among women with IDD than among those with physical disabilities as a whole.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…This study builds on recent findings indicating that women with disabilities are at greater risk for SMM and/or mortality than women without disabilities 11–13 Brown et al 13 also found that risk was greater for women with IDD than for those with physical or sensory disabilities. We found similar patterns of increased risk for SMM among women with disabilities overall, and greater risk among women with IDD than among those with physical disabilities as a whole.…”
Section: Discussionsupporting
confidence: 62%
“…For example, prior research has found increased odds of gestational hypertension and/or preeclampsia among women with IDD, 12,[20][21][22][23]25 and increased risk of gestational diabetes, preeclampsia and VTE among women with physical disabilities. 12,17 We found similar patterns with regard to gestational diabetes and preeclampsia. Numbers were small for our analyses of VTE; nonetheless, the pattern we observed was worrying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recently, two different groups have shown that severe maternal morbidity (SMM) is increased among women with disabilities across the spectrum of physical, intellectual, developmental and sensory disabilities. 2,3 In this issue of Paediatric and Perinatal Epidemiology, Horner-Willi and colleagues 4 essentially confirm these findings and make an important addition by conducting analyses in subgroups of individuals with disabilities, for example considering people with vision and hearing impairments separately and stratifying analyses for physical disabilities by the underlying cause. Using a large, population-based California dataset, they found an almost threefold increased risk of SMM among WWD overall.…”
mentioning
confidence: 91%
“…At the time of the workshop, pregnancy rates among women with disabilities were unknown; we now know that pregnancy prevalence is comparable between women with and without disabilities 7 . In 2010, while there were ample data showing that women with disabilities, in general, were more likely to have socioeconomic disadvantages, difficulty accessing medical care (especially reproductive care) and unmet medical needs, we did not know whether these factors applied specifically to pregnant women with disabilities; we now know that they do 1–3 …”
mentioning
confidence: 99%